Heteromerization between α2A adrenoceptors and different polymorphic variants of the dopamine D4 receptor determines pharmacological and functional differences. Implications for impulsive-control disorders. (August 2021) - Casadó-Anguera, Verònica; Moreno, Estefanía; Sánchez-Soto, Marta; Cai, Ning Sheng; Bonaventura, Jordi; Homar-Ruano, Patricia; Rubinstein, Marcelo; Cortés, Antoni; Canela, Enric I.; Ferré, Sergi; Casadó, Vicent
Abstract: Polymorphic alleles of the human dopamine D4 receptor gene ( DRD4 ) have been consistently associated with individual differences in personality traits and neuropsychiatric disorders, particularly between the gene encoding dopamine D4.7 receptor variant and attention deficit hyperactivity disorder (ADHD). The α2A adrenoceptor gene has also been associated with ADHD. In fact, drugs targeting the α2A adrenoceptor (α2A R), such as guanfacine, are commonly used in ADHD treatment. In view of the involvement of dopamine D4 receptor (D4 R) and α2A R in ADHD and impulsivity, their concurrent localization in cortical pyramidal neurons and the demonstrated ability of D4 R to form functional heteromers with other G protein-coupled receptors, in this study we evaluate whether the α2A R forms functional heteromers with D4 R and weather these heteromers show different properties depending on the D4 R variant involved. Using cortical brain slices from hD4.7 R knock-in and wild-type mice, here, we demonstrate that α2A R and D4 R heteromerize and constitute a significant functional population of cortical α2A R and D4 R. Moreover, in cortical slices from wild-type mice and in cells transfected with α2A R and D4.4 R, we detect a negative crosstalk within the heteromer. This negative crosstalk is lost in cortex from hD4.7 R knock-in mice and in cells expressing the D4.7 R polymorphic variant. We also show a lack of efficacy of D4 R ligands to promote G protein activation and signaling only within the α2A R-D4.7 R heteromer. Taken together, our results suggest that α2A R-D4 R heteromers play a pivotal role in catecholaminergic signaling in the brain cortex and are likely targets for ADHD pharmacotherapy. Graphical Abstract: ga1 Highlights: α2A adrenoceptors can form oligomeric complexes with D4.4 R and D4.7 R variants. α2A R-D4 R heteromers are expressed in mouse cerebral cortex. The negative crosstalk detected in α2A R-D4.4 R is lost in α2A R-D4.7 R heteromers. D4 R agonists are unable to promote signaling within the α2A R-D4.7 R heteromer.